Analisis Isi Sikap Sosial Dalam Buku Ajar Pendidikan Agama Islam Dan Budi Pekerti - Nurochim Nurochim; Siti Ngaisah (Al Hikmah: Journal of Education, 2021)
The purpose of this study is to find the embodiment of social attitudes that will be achieved through textbooks. The study in this article uses content analysis of textbooks used in PAI and Budi Pekerti learning. People's lives today are surrounded by various challenges. The challenge is in the form of high social and economic disparities. In addition, in the Indonesian context, society consists of various ethnic, racial, and religious backgrounds. At this time, society in the framework of globalization is facing acculturation of western culture that is different from local conditions. Therefore, it is important that social attitudes are formed through the learning process at school. One of the efforts is the learning of Islamic religion and manners, where Islamic teachings not only teach human relations with God, but also relationships with fellow humans. The results of the study show that social attitudes are reflected in graduate competency standards, content standards, core competencies and basic competencies, and textbooks. The concept of social attitudes in the form of honesty, courtesy, empathy, and responsibility. These attitudes are manifested in all religious activities and daily activities.Tujuan kajian ini adalah untuk menemukan perwujudan sikap sosial yang akan dicapai melalui buku ajar. Kajian dalam artikel ini menggunakan analisis isi buku teks yang digunakan dalam pembelajaran PAI dan Budi Pekerti. Kehidupan masyarakat pada saat ini dilingkupi oleh berbagai tantangan. Tantangan tersebut berupa masih tingginya kesenjangan sosial dan ekonomi. Selain itu dalam konteks Indonesia masyrakat terdiri dari berbagai latar belakang suku, ras, dan agama. Pada saat ini juga masyarakat dalam kerangka globalisasi menghadapi akulturasi budaya barat yang berbeda dengan kondisi lokal. Oleh sebab itu penting sikap sosial dibentuk melalui proses pembelajaran di sekolah. Salah satu upayanya adalah pembelajaran agama islam dan budi pekerti, di mana ajaran Islam tidak hanya mengajarkan relasi manusia dengan Allah, namun juga relasi dengan sesama manusia. Hasil kajian menunjukkan bahwa sikap sosial tergambar mulai standar kompetensi lulusan, standar isi, kompetensi inti dan kompetensi dasar, dan buku ajar. Konsep sikap sosial berupa jujur, santun, empati, dan bertanggung jawab. Sikap-sikap tersebut diwujudkan dalam segala aktivitas peribadahan dan aktivitas keseharian.